154k views
3 votes
Nathaniel is using the quadratic formula to solve 0 = x2 + 5x - 6. His steps are shown below. Table showing 3 steps to solve an equation using the quadratic formula. What are the solutions to the equation? x = –1, 6 x = –6, 1 x = –22, 27 x = –27, 22

User Satiago
by
6.8k points

2 Answers

3 votes

Answer:

BBBBBBBBBBBBBBBBBBBBBBBBBBBBBBBBBBBBBBBBB

Explanation:

User Kati
by
7.0k points
4 votes

Answer:

x= -6, 1

Explanation:

To solve;

X² + 5x - 6

Using the quadratic formula, we need to follow the steps below;

First compare the equation given with the standard equation ax² + bx + c

a= 1 b=5 and c = -6

Write down the quadratic formula

x = -b ±√b² - 4ac /2a

x = -5 ±√5² - 4(1)(-6) /2(1)

x = -5 ±√25+24 /2

x = -5 ±√49 /2

x = -5 ± 7/2

Either x = -5-7 /2 or x = -5 + 7 /2

Either x = -12/2 or x= 2/2

Either x = -6 or x=1

x = -6 or 1

x= -6, 1

User Daniel Marcotte
by
5.5k points